Evaluasi dan Pengembangan Jaringan Distribusi Air Minum di PDAM Tirta Bhagasasi: Studi Kasus Cabang Babelan dan Cabang Sukatani: indonesia - Mistoro, Niesa Hanum; Yulianto, Andik; Wantoputri, Noviani Ima (UII, 2025)
Rapid population growth in the Babelan and Sukatani areas of Bekasi Regency has significantly increased the demand for clean water, posing a challenge for PDAM Tirta Bhagasasi in maintaining a reliable and sustainable drinking water supply. This study aims to evaluate the performance of the existing water distribution network and propose an optimized development plan to meet projected demand through 2041. The methodology includes population and water demand projections, evaluation of Water Treatment Plant (WTP) capacity, hydraulic simulation using EPANET 2.0, and cost estimation for network development. The results show that by 2041, the population in Babelan and Sukatani is projected to reach 418,390 and 149,700 people respectively, with corresponding water demands of 481.8 L/s and 172.5 L/s. The existing WTP capacities are insufficient, particularly in Sukatani, which currently operates at only 44 L/s. Hydraulic simulation indicates that a looping distribution system is more effective than a branching system in improving water pressure and reducing losses. However, implementing a looping system requires a higher investment, estimated at approximately IDR 15 billion, compared to IDR 10 billion for a branching system. Given these findings, the study recommends that PDAM Tirta Bhagasasi prioritize increasing WTP capacity and adopt a looping-based distribution network to ensure long-term service reliability, particularly in high-growth areas. This approach offers both technical and economic benefits for future water supply planning and can serve as a model for other regions facing similar challenges.